L’iscrizione latina sulla facciata di palazzo Dedi-Staurenghi a Fossombrone. Cultura identitaria e antiquaria tra influssi e ricezioni di secondo Quattrocento - Aureli, Giorgia (Opus Incertum, 2022)
The façade of Palazzo Dedi Staurenghi in Fossombrone represents a significant example of the fifteenth-century architectural trends that derived from the cultural and artistic renewal policies promoted in Urbino and its surroundings by Federico da Montefeltro. Although interrupted, the Latin inscription in the frieze of the windows reveals the professional training and the personal interests of the patron, the jurist Paolo Dedi, an important member of the humanistic and antiquarian cultural society which developed in the town during this time. The paper aims to analyse the role played by the inscription in the general image of the façade and in close relation with the urban space of the square in front of it. Considering the local cultural context, as well as other contemporary building examples, the essay also deals with archival research on the patronage and the humanistic interest in classical epigraphy, focusing on cultural references, treatises and handbooks of Roman capital letters.